SOSIALISASI BIDAI (TIRAI) MELALUI INTERNET DAN DIGITAL MARKETING DALAM UPAYA MENINGKATKAN EKONOMI MASYARAKAT DESA RANTAU DURIAN 1 KECAMATAN LEMPUING JAYA KABUPATEN OGAN KOMERING ILIR (OKI) - Mail Hilian Batin; Maria Ulfa; Raihan Taneta Putra; Marindah Marindah; Novika Sari (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Today, technology has an essential role in economic progress, especially for small and large scale entrepreneurs. The utilization of technology is crucial to support the efficiency and effectiveness of sales. Urban communities only felt the presence of this technology but not for those who live in rural areas. The approach taken uses socialization about the importance of the role of the internet and digital marketing for the craftsmen of Palm oil palm midrib artisans in Rantau Durian 1 Village, Lempuing Jaya District, OKI Regency, South Sumatra. The results of the socialization gave a positive impression to the craftsmen. They gave a fresh breeze of their sustainability in the business of the palm fronds themselves, and their income hopes were far better than before knowing internet marketing. So far, the traditional marketing system where the craftsmen sell directly to the market using trucks, then it takes a long time to sell all of their merchandise.